2022
DOI: 10.3389/fphys.2022.839140
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Ca2+-Activated cAMP/PKA Signaling Prevents Hydroxychloroquine-Induced Bradycardia of the Cardiac Pacemaker

Abstract: Bradycardia or tachycardia are known side effects of drugs that limit their clinical use. The heart pacemaker function which control the heart rate under normal conditions is determined by coupled clock system. Thus, interfering with specific clock mechanism will affect other clock mechanisms through changes in interconnected signaling and can lead to rhythm disturbance. However, upregulation of a different clock components can compensate for this change. We focus here on hydroxychloroquine (HCQ), which has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Given the role that L-type calcium current plays in excitation-contraction coupling, as major trigger for calciuminduced calcium release from the sarcoplasmic reticulum, a decrease in calcium influx via L-type calcium channels could significantly affect intracellular calcium concentration and impair cardiac contraction (Eisner et al, 2017). The recent observation that HCQ decreases total calcium influx and calcium transient magnitude in cardiomyocytes (Oguntuyo et al, 2022;Segal et al, 2022), together with HCQ and AZM effect on calcium transient upstroke velocity in human induced pluripotent stem cell-derived cardiomyocytes (Charrez et al, 2021), further supports the ability of both drugs to reduce intracellular calcium concentration and affect contractility.…”
Section: The Calcium Channel Agonist Bay K8644 Prevents and Reverses ...mentioning
confidence: 99%
“…Given the role that L-type calcium current plays in excitation-contraction coupling, as major trigger for calciuminduced calcium release from the sarcoplasmic reticulum, a decrease in calcium influx via L-type calcium channels could significantly affect intracellular calcium concentration and impair cardiac contraction (Eisner et al, 2017). The recent observation that HCQ decreases total calcium influx and calcium transient magnitude in cardiomyocytes (Oguntuyo et al, 2022;Segal et al, 2022), together with HCQ and AZM effect on calcium transient upstroke velocity in human induced pluripotent stem cell-derived cardiomyocytes (Charrez et al, 2021), further supports the ability of both drugs to reduce intracellular calcium concentration and affect contractility.…”
Section: The Calcium Channel Agonist Bay K8644 Prevents and Reverses ...mentioning
confidence: 99%
“…To demonstrate that LCR characteristics are affected by changes in the beating rate, hiPSC-CMs were treated with HCQ, which causes bradycardia ( Capel et al, 2015 ). We recently showed that HCQ-induced bradycardia was caused by a direct effect on the M clock and an indirect effect on the Ca 2+ clock ( Segal et al, 2022 ). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Single, spindle-shaped SANCs were isolated from the hearts of white New Zealand rabbits weighing 2.3-2.7 kg, as previously described [8,9]. Briefly, rabbits were sedated with ketamine and xylazine (0.1 mL/kg each) and anesthetized with sodium pentobarbital (200 mg/mL) diluted with heparin, administered through an intravenous cannula.…”
Section: San Cell Isolation and Culturementioning
confidence: 99%
“…Ca 2+ cycling in single spontaneously beating SANCs was recorded by monitoring the fluorescence of the Ca 2+ indicator dye, Fluo-4 AM (Thermo Fisher Scientific, Waltham, MA, USA), using a LSM880 confocal microscope, as previously described [8]. SANCs were loaded with 5 µM Fluo-4 AM for 20 min, in the dark, at room temperature, and then washed with a 37 • C HEPES solution (140 mM NaCl, 5.4 mM KCl, 2 mM MgCl 2 , 5 mM HEPES, 1.8 mM CaCl 2 and 10 mM glucose, titrated to pH 7.4 with NaOH).…”
Section: Ca 2+ Imaging and Measurementsmentioning
confidence: 99%